2007
DOI: 10.1007/s10544-007-9114-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of surface modification on microelectrode arrays for in vitro cell culture

Abstract: This study aims to investigate surface-modified microelectrodes on the microelectrode arrays (MEAs) for neuronal interfaces with in vitro cell culture. The polyimide (PI) MEA was fabricated by using micro-electro-mechanical systems (MEMS) techniques. Self-assembled monolayers (SAMs) of 11-mercaptoundecanoic acid (MUA) were utilized to modify the microelectrode surface of the MEA. The SAMs' modified surface of microelectrodes offered a reliable interface to immobilize biological ligands through covalent bonding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 35 publications
1
17
0
1
Order By: Relevance
“…Previously, it was shown that determination of cell damage, cell growth, and cell morphology, could serve as preliminary indices for evaluating the non-cytotoxicity of medical devices [25, 35, 36]. In our study, characterization of cells cultured in the degraded 3D matrix with a perfusion system on MEA indicated cell survival and growth in the in-vitro 3D matrix.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…Previously, it was shown that determination of cell damage, cell growth, and cell morphology, could serve as preliminary indices for evaluating the non-cytotoxicity of medical devices [25, 35, 36]. In our study, characterization of cells cultured in the degraded 3D matrix with a perfusion system on MEA indicated cell survival and growth in the in-vitro 3D matrix.…”
Section: Discussionmentioning
confidence: 67%
“…The impedance measurement is essential for validating successful fabrication and chemical modification of self-designed MEAs when AFM or SEM methods are generally unsuitable for all electrode samples [25, 26, 36, 39]. In accordance with our previous experience, it is commonly suggested that the total impedance exceeding 800 kΩ after surface modification should be considered a modification failure [25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations